Real-Time Implementation of an Internet of Things-Based Rose Eco-Enzyme Fermentation Monitoring System for Women Farmers Group - Wahyu Eka Kiswardani; Azizia Gia Mutiasari; Muhammad Farhansyah Mondari; Krisnayanti Aditasari (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Ngliman Village is one of the largest rose-producing villages in the Kediri Residency area. However, the surplus of rose harvests has resulted in a large amount of rose petals not being optimally utilized, potentially becoming organic waste. One of the alternative solutions for utilizing this waste is through the fermentation of eco enzyme made from rose petals. The fermentation process conducted by the Women Farmers Group (Kelompok Wanita Tani/KWT) is still performed manually, making it difficult to monitor fermentation conditions and increasing the risk of fermentation failure. This study aims to implement a real-time eco enzyme fermentation monitoring system based on the Internet of Things (IoT). The system was designed using an ESP32 microcontroller with a DHT22 sensor for temperature monitoring and an MPX Pressure Sensor for monitoring fermentation gas pressure. Monitoring data are transmitted through the internet network and displayed on a web-based dashboard in real-time. The results show that the system is capable of reading, processing, and displaying temperature and gas pressure monitoring data effectively during the fermentation process. The implementation of the IoT-based monitoring system can support a more effective, structured, and efficient fermentation monitoring process while minimizing the risk of fermentation failure at the community scale.